Processability Assessment of HDPE/UHMWPE Blends for Fused Deposition Modeling Applications - Subhedar, Prajakta; Padmanabhan, Divya; Agrawal, Richa (Journal of Research Updates in Polymer Science, 2025)
Ultra-high molecular weight polyethylene (UHMWPE) is highly regarded for its superior mechanical properties, chemical resistance, and biocompatibility. However, its extremely high melt viscosity inhibits direct use in extrusion-based additive manufacturing techniques like fused deposition modeling (FDM). This study explores enhancing the processability and FDM compatibility of UHMWPE by blending it with high-density polyethylene (HDPE) and polyethylene glycol (PEG). Three formulations were assessed: neat HDPE, a 70:30 (w/w) binary HDPE/UHMWPE blend, and a ternary blend of HDPE/UHMWPE/PEG at 60:30:10 (w/w/w). Consistent with prior literature, pure HDPE displayed stable extrusion and excellent filament quality facilitating high-fidelity prints. The binary blend allowed filament formation but showed rough surface morphology and compromised print quality due to poor miscibility, echoing similar challenges reported in polymer blend studies. The ternary blend, intended to improve melt flow via PEG plasticization, resulted in erratic filament diameter and unreliable extrusion, highlighting the delicate balance needed in additive incorporation. These outcomes confirm that HDPE incorporation improves UHMWPE extrusion capabilities; however, advanced compatibilization techniques and refined processing, such as twin-screw extrusion, remain essential for achieving dependable FDM performance. The findings offer critical insights for designing UHMWPE-based filaments tailored for biomedical and industrial additive manufacturing applications.